Mobile data offloading: an agent-based modelling study on the effectiveness of Wi-Fi offloading - Yorick Breukers; Mark de Reuver; Michel Oey; Harry Bouwman (International Telecommunications Society (ITS), 2015)
To reduce the load on cellular networks, offloading to Wi-Fi has long been discussed as a technological solution. Despite advances in scheduling algorithms and incentive schemes, most mobile operators do not actively promote Wi-Fi offloading and most Wi-Fi usage is limited to stationary in-home contexts of use. This study assesses the proportion of users on the street that can be offloaded to Wi-Fi access points, taking into account different city topologies, speed of movement and technical characteristics of Wi-Fi access points. We show that the proportion of users on the street that can be offloaded to Wi-Fi heavily depends on their speed of moving around, the reach of access points and the delay in logging on to access points. However, even when using standard configurations for access points, base stations and smartphones, half the outdoor users can be offloaded to Wi-Fi. These results are consistent for any type of realistic topology of roads in the city. Based on the results, operators are recommended to promote Wi-Fi offloading as it massively reduces the load on cellular networks.
Keywords: 330